2023
DOI: 10.1177/25168657231199893
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation in Cancer: Epigenetic View of Dietary and Lifestyle Factors

Mohsen Maleknia,
Nooshin Ahmadirad,
Fereshteh Golab
et al.

Abstract: Background: Alterations in DNA methylation play an important role in cancer development and progression. Dietary nutrients and lifestyle behaviors can influence DNA methylation patterns and thereby modulate cancer risk. Introduction: To comprehensively review available evidence on how dietary and lifestyle factors impact DNA methylation and contribute to carcinogenesis through epigenetic mechanisms. Materials and methods: A literature search was conducted using PubMed to identify relevant studies published bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 113 publications
0
1
1
Order By: Relevance
“…In addition, other factors, including poor dietary habits, weight gain, smoking, and comorbid substance use, usually associated with schizophrenia 35 , 36 might be able to influence epigenetics. 37 However, neither the present nor previous studies controlled for any of these factors. Notably, the majority of DLPFC samples, in which we observed enhanced expression of permissive H3K9ac, H3K27ac, and H3K4me3 in schizophrenia, came from men.…”
Section: Discussioncontrasting
confidence: 58%
“…In addition, other factors, including poor dietary habits, weight gain, smoking, and comorbid substance use, usually associated with schizophrenia 35 , 36 might be able to influence epigenetics. 37 However, neither the present nor previous studies controlled for any of these factors. Notably, the majority of DLPFC samples, in which we observed enhanced expression of permissive H3K9ac, H3K27ac, and H3K4me3 in schizophrenia, came from men.…”
Section: Discussioncontrasting
confidence: 58%
“…However, Cox proportional hazard analysis showed no evidence that lifestyle-associated factors and PRS directly interacted with each other. Numerous studies have recently reported the relationship between epigenetic markers and lifestyle-associated factors, such as stress, smoking, alcohol use, and diet [ 37 ]. Various environmental factors epigenetically remodel the genome without altering its DNA sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence suggests that dysregulation of DNMT activities is associated with aberrant hypo-or hypermethylation and has profound effects on gene transcription. Along these indications, recent www.nature.com/scientificreports/ investigations continue to unveil the pivotal role of aberrant DNA methylation and related epigenetic processes in cancer initiation, promotion, and progression [35][36][37] . Moreover, there are several reports that highlight a role of DNA methylation in regulating multiple facets of cancer metastatic process 4,[32][33][34]38 .…”
Section: Discussionmentioning
confidence: 99%